(untitled) (Research, Society and Development, 2021)
Objective: to analyze the scientific productions that describe about signs and symptoms prevalent in patients with heart disease who require nursing care. Method: It is a literature review carried out in January-February 2018. The articles analyzed were published between 2013 and 2017. The collected material were from LILACS, BDENF, MEDLINE, PUBMED and in the virtual library SciELO databases. Results: A total of 23 articles were selected. Among the signs and symptoms mentioned, fatigue represented 47.82%; 39.13% showed dyspnea and changes in the respiratory pattern; 30.43% cited precordial pain, depression and/or depressive symptoms; edema, nausea, vomiting and gastrointestinal disorders appeared in 17.39%; 13.04% indicated heart rhythm changes, psychic/anxiety and sleep disorders; 8.70% referred to tiredness, as well to congestion, and to health history and dressings; 4.35% demonstrated aversion to food, weight gain or loss, ventricular ejection fraction, lipothymia, hemodynamic instability, weakness and inaccurate information acquisition ability. Conclusion: the signs and symptoms listed may constitute a relevant set of indicators that will contribute to the prediction of complications in patients with heart disease and, consequently, improve the management of nursing care for these patients.